Economic evaluation of composting - Olga Kharaishvili; Dali Baidauri; Tinatin Darsavelidze; Lali Baidauri; Lina Giorgadze; Natia Darbaidze (Progress in Science, 2024)
Environmental protection and their rational management from waste today is a serious problem in the world In the future, the Ministry of Environment Protection and Agriculture of Georgia plans to direct important material resources to raising public awareness on waste management, among other things, because people are responsible for the problem of anthropogenic littering. Today in Georgia there is no separation and sorting of waste, which is why poisonous substances are found in landfills. There is a lot of research and materials about compost, compost is considered the best fertilizer, it is environmentally friendly, it is cheap, it is made from waste that we have at home, which we will use instead of throwing away, be careful and we will create an ecologically clean environment.